Becoming a father : contemporary social developmental, and clinical perspectives - Shapiro, Jerrold Lee; Diamond, Michael J.; Greenberg, Martin (New York, N.Y. : Springer, 1995)
ISBN 0-8261-8400-6
Keywords: obiteljska pedagogija -- roditeljstvo -- očinstvo -- sociokulturna perspektiva